2016
DOI: 10.1144/sp428.11
|View full text |Cite
|
Sign up to set email alerts
|

DOBRE-2 WARR profile: the Earth's upper crust across Crimea between the Azov Massif and the northeastern Black Sea

Abstract: The DOBRE-2 wide-angle reflection and refraction profile was acquired in June 2007 as a direct, southwestwards prolongation of the 1999 DOBREfraction'99 that crossed the Donbas Foldbelt in eastern Ukraine. It crosses the Azov Massif of the East European Craton, the Azov Sea, the Kerch Peninsula (the easternmost part of Crimea) and the northern East Black Sea Basin, thus traversing the entire Crimea–Caucasus compressional zone centred on the Kerch Peninsula. The DOBRE-2 profile recorded a mix of onshore explosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 38 publications
1
15
0
2
Order By: Relevance
“…A local seismic tomography study of this same area centred on the Kerch Peninsula and reported by Gobarenko et al (2015) complements the Starostenko et al (2016) geophysical study. The resulting three-dimensional P-and S-wave velocity models, for an area of c. 200 × 100 km (east-west and north-south, respectively) with a depth of c. 40 km ( Fig.…”
Section: 'Black Sea' Domain Of the Eastern Black Sea -Caucasus Tectonsupporting
confidence: 60%
See 2 more Smart Citations
“…A local seismic tomography study of this same area centred on the Kerch Peninsula and reported by Gobarenko et al (2015) complements the Starostenko et al (2016) geophysical study. The resulting three-dimensional P-and S-wave velocity models, for an area of c. 200 × 100 km (east-west and north-south, respectively) with a depth of c. 40 km ( Fig.…”
Section: 'Black Sea' Domain Of the Eastern Black Sea -Caucasus Tectonsupporting
confidence: 60%
“…Sydorenko et al (2016) report a geological interpretation of a regional seismic reflection profile acquired along the same transect and in association with the DOBRE2 WARR profile (labelled 8 in Fig. 1) reported by Starostenko et al (2016) and the resulting velocity model of the latter is superimposed on the former. The regional basin architecture from the Azov Sea, crossing the Kerch Peninsula into the Black Sea as far south as the eastern Black Sea deep basin, consists of a series of basement structural highs separating a series of sedimentary depocentres and is mainly a consequence of the compressional tectonic regime affecting the area since the Eocene.…”
Section: 'Black Sea' Domain Of the Eastern Black Sea -Caucasus Tectonmentioning
confidence: 91%
See 1 more Smart Citation
“…Several regional-scale compressional episodes affected the entire Black Sea during the Cenozoic (e.g. Stovba et al 2009). Finally, there are possibly stratigraphic traps within the Miocene-Pliocene sequence outboard from the Tuapse foldbelt (Fig.…”
Section: Gudautamentioning
confidence: 99%
“…According to the DOBRE regional seismic profiles (see Fig. 2, a), the crust below the Crimean peninsula is 40-50 km thick and gradually thins southward [Yegorova, Gobarenko, 2010;Starostenko et al, 2015Starostenko et al, , 2016. The Scythian crystalline basement was drilled to 0,2-2,0 km depth [Muratov, 1960]; the hanging Paleozoic sedimentary rocks -also only known from wells -are 1-5 km thick [Muratov, Sydrenko, 1969].…”
mentioning
confidence: 99%